2014
DOI: 10.1108/jmp-06-2012-0193
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital, Big Five traits, and employee outcomes

Abstract: Purpose – The aim of this paper was to examine the incremental validity of positive psychological capital (PsyCap) in predicting several important employee outcomes while controlling for a full range of personality traits. Design/methodology/approach – Using a cross-sectional field study design, the authors collected data from 373 employees in South Korea. Findings – Hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 50 publications
5
94
0
14
Order By: Relevance
“…Such employees are satisfied with their job and career in the current organization and their life in general, because the availability of personal resources is likely to enable them to fulfill the requirements of the job, pursue career development opportunities in the current organization, and have life satisfaction. These results are also in line with limited empirical studies in the current literature Choi and Lee, 2014;Lehoczky, 2013).…”
Section: Strengths Of the Study And Evaluation Of Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…Such employees are satisfied with their job and career in the current organization and their life in general, because the availability of personal resources is likely to enable them to fulfill the requirements of the job, pursue career development opportunities in the current organization, and have life satisfaction. These results are also in line with limited empirical studies in the current literature Choi and Lee, 2014;Lehoczky, 2013).…”
Section: Strengths Of the Study And Evaluation Of Findingssupporting
confidence: 89%
“…Fourth, since the overwhelming majority of studies on PsyCap emerge from samples in the United States, there is a need for more empirical research that investigates PsyCap in different cultural settings concerning its contextual applicability (Choi and Lee, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study which examined the incremental validity of psychological capital in predicting several important employee outcomes by suppressing the effects of big-five personality dimensions revealed that employee's psychological capital is related to their perceived performance, turnover intention, work happiness & subjective well being, even after controlling for the Big Five Personality traits (Choi and Lee, 2014). The current study incorporates both Another research aimed to delve into the relationships of coping strategies with Positive Psychological Capital and Big Five among undergraduate university students which concluded that positive psychological capital and big five were found to be significantly related to coping mechanisms except neuroticism, while high extraversion, openness & conscientiousness individuals engaged in more problem-focused coping and finally concluded that personality factors and positive psychological capital has emerged as important constructs for detecting coping mechanisms (Khan et al, 2011).…”
Section: Combined Effects Of Big Five Positive Psychological Capitalmentioning
confidence: 99%
“…The overwhelming majority of empirical studies on hope have been conducted in the United States. This calls for research investigating psychological resources in different cultures (Choi & Lee, 2014). Thus, it is vital to explore the feasibility of hope as a determinant of individual level outcomes in newer work settings.…”
Section: Introductionmentioning
confidence: 99%